Design and Efficacy of Solar Disinfection System for Improved Rural Household Water Treatment - Russel C.G. Chidya (SDEWES Centre, 2021)
This study aimed at designing, prototyping and testing the effectiveness of a solar disinfection system for improved rural household water treatment. The system was constructed using local materials. The effectiveness and efficiency of the system to kill microorganisms were determined by using contaminated raw water samples collected from rural areas. The prototype raised the bottle water temperature from 24.3 to 66 °C. After 3 hours of exposure to intense sunlight, the water samples registered no total and faecal coliform counts in line with allowable drinking water limits by Malawi Standards and the World Health Organization. When loaded with 12 L of the contaminated water, the system scored a 10.2 % efficiency. The prototype reached disinfecting temperature faster (80 minutes) under intense sunlight conditions and worked effectively well with water of low turbidity levels. The prototype was cost-effective and easy to use, hence to be promoted for improved rural household water treatment.